2013
DOI: 10.3892/ijmm.2013.1300
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase- and angiogenesis-related gene responses to irradiation in human umbilical vein endothelial cells

Abstract: In this study, we investigated the effects of ionizing radiation (IR) on human umbilical vein endothelial cells (HUVECs) in the context of senescence. HUVECs at passage number (PN)1, PN2 and PN3 were exposed to irradiation (2 Gy). The growth rate of the HUVECS was measured by proliferation assay and senescence-associated β-galactosidase assay was used to measure the number of senescent cells. Telomerase activity and the expression of telomerase- and angiogenesis-related genes were measured by telomerase assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…EC senescence seems to drive dysfunctional phenotypes through upregulation of several canonical SASP factors, such as IL-6, TNF-α, and PAI-1, leading to dysfunction in other vascular cells [108,109]. Angiogenesis is another aspect of endothelial function, protecting tissues against ischemia in ischemic heart disease and peripheral arterial diseases, primarily through vascular endothelial growth factor (VEGF) [110], fibroblast growth factor (FGF) [111], and hypoxia-inducible factor (HIF) 1α [112]. Senescent ECs decrease expression of these factors in vessels due to signaling through the p53-p21 senescence pathways, as evidenced by increased angiogenesis after this pathway is inhibited [96].…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…EC senescence seems to drive dysfunctional phenotypes through upregulation of several canonical SASP factors, such as IL-6, TNF-α, and PAI-1, leading to dysfunction in other vascular cells [108,109]. Angiogenesis is another aspect of endothelial function, protecting tissues against ischemia in ischemic heart disease and peripheral arterial diseases, primarily through vascular endothelial growth factor (VEGF) [110], fibroblast growth factor (FGF) [111], and hypoxia-inducible factor (HIF) 1α [112]. Senescent ECs decrease expression of these factors in vessels due to signaling through the p53-p21 senescence pathways, as evidenced by increased angiogenesis after this pathway is inhibited [96].…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Increasing evidence has shown that telomerase expressions are associated with VEGF expressions in both normal and cancer cells [28,[32][33][34][35]. For instance, telomerase activities, as well as hTERT and VEGF expressions, were down-regulated during serial passage in irradiated human umbilical vein endothelial cells [38]. Expressions of hTERT were significantly associated with VEGF expressions in prostate, gastric [37], and breast cancers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real time RT-PCR, PCR-based TRAP analysis, linear range of TRAP assay are most often used methods. [2627282930] Some investigators have also used RT-PCR for assessment of telomerase gene expression in HUVECs in instances like assessment of telomerase activity by RT-PCR after induction of TERT over-expression. [3132] Indeed, RT-PCR was used to assess telomerase gene expression in HUVECs after administration of agents, which increase telomerase gene expression as 17beta-estradiol.…”
Section: Discussionmentioning
confidence: 99%